Miernik produktywności pracy w kontrolingu zysku i zyskowności - Jędrzejczyk, Marcin; Dobija, Mieczysław (Wage Productivity Measure in Profit and Profitability Controlling, 2007)
Profit controlling is a very important process for the activity of an enterprise. Because it is very hard to control profit, as it is single value estimated at the end of the accounting period, the new method must be developed to fulfill the demand of continuous control. The paper presents the method based on analytic production function from which it is possible to extract single measure of profitability of the company. The measure, called wage productivity, can represent the value of several crucial ratios that characterize economic condition of an enterprise. As shown in the paper wage productivity WP is the composition of five ratios, including synthetic management variable M. Its growing value is the strong premise to the opinion of the good management in the company and good condition of the whole company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 204-214